Evaluation of the modified combined glucocorticoid toxicity index in rheumatoid arthritis: Preliminary data - V. V. Lebedeva; Yu. V. Muravyev; S. I. Glukhova (Научно-практическая ревматология, 2020)
Objective: to assess whether the modified combined glucocorticoid (GC) toxicity index (MCGTI) can be used to analyze adverse reactions (ARs) to GCs administered in the management of rheumatoid arthritis (RA).Subjects and methods. The investigation enrolled 71 RA patients (57 females, 14 males; mean age, 51.7+15.2 years). All the patients met the ACR/EULAR classification criteria and took GCs (the median duration of GC treatment duration was 7.1 [0.9; 12.0] years). In addition to the standard clinical, laboratory, and instrumental indicators, the daily and cumulative doses of GCs (in prednisolone equivalent) and MCGTI were analyzed.Results and discussion. The value of MCGTI statistically significantly correlated with treatment duration (r=0.411), age (r=0.384), and the cumulative dose of GCs (r=0.361), but did not correlate with their maximum dose (r=0.06). A ROC analysis showed that the critical level of the cumulative dose of GCs in relation to MCGTI was 17,337.5 mg.Conclusion. MCGTI correlates with cumulative dose (making it possible to establish its critical level), treatment duration, and age, which is the basis for further study of whether this can be applied in clinical practice to evaluate, predict, and prevent ARs.